Business Model Fintech Aggregator In Indonesia (Cermati.com Case Study) - Yossi Artika Puti (Publisher Cv. Inara Colaboration with www.stie-sampit.ac.id, 2024)
Development in technology is increasingly rapid and continues to bind human life, which also encourages technological innovation in financial services usually called Financial Technology or Fintech. Fintech is considered able to reach people who so far are still not reached by banking. The number of companies undertaking fintech businesses in Indonesia is increasing and this increase is one of the factors driving financial inclusion in Indonesia. One of those participating in the use of this technology is dealing as Fintech Aggregator, namely fintech that gathers information by providing comparisons of benefits, facilities, protection and prices available in bank and non-bank financial institution products. This research focuses on finding out about the Fintech Aggregator business model in Indonesia based on the study of 9 blocks of Business Model Canvas and 4 pillars of Value Design Model through case studies on Cermati.com. From the results based on the two business models above, it can be found out that each of the available block elements has described business activities in detail, in which based on the Business Model Canvas, the company has been able to effectively and efficiently determine its business strategy. Meanwhile, if viewed from the Value Design Model, the entire ecosystem in the company is in accordance with each other and moves in the same direction and has mutual connection between its 4 pillars. In this way, value creation can be carried out on the basis of complementary relationships.